One, no one, one hundred thousand: democratic meanings of constituent power - Rosa, Gabriela Rodrigues da Guia (2024)
The idea that constituent power belongs to the people structures the way we think about democracy. But even though constituent power and democracy seem to be necessarily connected for democratic ruling to be legitimate, this was not always the case in history. This dissertation addresses this problem by demonstrating, first, that popular constituent power emerged in our political vocabulary long before democracy came to be the preferred form of the constitutional state. By demonstrating that constituent power is defined in contrast with its constituted counterpart, it stresses that there is also a great difference between the people\'s authority to institute a political community and its possibilities to exercise political power within the constituted order. Taking up this discussion under the light of contemporary democratic theory, this research also stresses there are two main possibilities to within the definition of popular constituent power: it either incorporates sovereignty as part of its meaning, or it rejects it altogether for its unifying effects. Generally represented by Carl Schmitt\'s and Hannah Arendt\'s theories, these positions also appear in the works of political theorists such as Antonio Negri, Andrew Arato and Andreas Kalyvas. An overview of their conceptions of constituent power then highlights, in each case, their specific demand for political participation leading to democratic constitutional processes